Cascaded Microbottle Resonator and Its Application in Add–Drop Filter - Yiheng Yin; Yanxiong Niu; Lingling Dai; Ming Ding (IEEE Photonics Journal, 2018)
Whispering-gallery-mode (WGM) microresonators. reveal enormous potential applications in fields ranging from micro/nano-optics, integrated and quantum optics, to optical precision measurements. In this paper, we propose a novel cascaded WGM microresonator which is composed of two partially overlapped microbottle resonators. The distribution property of mode intensity and the variation characteristic of quality factors (Q factors) were analyzed theoretically, and demonstrated by evanescently exciting the microresonator with a tapered fiber at different axial positions. Based on the cascaded microbottle resonator, a stable add-drop filter was demonstrated, and the effective excitation properties of the modes in the microresonator were discussed for the first time. Due to the larger axial dimension, the proposed WGM microresonator could also find applications in strain sensors and time delay devices.